Evaluation of seasonal variation, effect of extraction solvent on phytochemicals and antioxidant activity on Rosmarinus officinalis grown in different agro-ecological zones of Kiambu County, Kenya - Zelipha N. Kabubii; James M. Mbaria; Mbaabu P. Mathiu; John M. Wanjohi; Evans N. Nyaboga (CABI Agriculture and Bioscience)
Abstract Background Rosemary (Rosmarinus officinalis) is a commonly used culinary herb with great potential applications in the pharmaceutical, food, and cosmetics industries because of its reported bioactive phytochemicals and antioxidant properties. The purpose of the study was to investigate the effect of seasonal variations in different agro-ecological zones (AEZs) on the phytochemical content and corresponding antioxidant activities of R. officinalis, to ascertain the best growth period at which the plant possesses the highest phytochemical components and most potent antioxidant property. The study also aimed at comparing different extraction solvents to establish the best extraction system for the bioactive compounds. Methods The leaves of R. officinalis were harvested from six purposively selected sites in four agro-ecological zones of Kiambu County, Kenya both in the wet and the dry seasons. Phytochemicals were extracted in 80% methanol, 80% ethanol, and distilled water. Total phenolic content (TPC), total flavonoids content (TFC), and total tannins content (TTC) were measured spectrophotometrically as gallic acid equivalent (GAE), rutin equivalent (RUTE) and tannic acid equivalent (TAE), respectively. The antioxidant activities were measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric-reducing antioxidant power (FRAP). The 80% ethanolic solvent was used to compare the phytochemical content and corresponding antioxidant activities of R. officinalis leaf samples collected from two consecutive seasons in different agro-ecological zones. Results The solvents showed no significant difference (P > 0.05) in TPC with ethanol repotting the highest followed by methanol and water ranging from 39.71 ± 6.77, 24.91 ± 5.15 and 24.91 ± 7.30 (mg/g GAE), respectively. The aqueous TFC (117.22 ± 3.64 mg/g RUTE) was the highest followed by ethanolic and methanolic with 34.72 ± 2.13 and 16.86 ± 2.80 mg/g RUTE, respectively. The TTC of water, methanol, and ethanol extracts were; 19.88 ± 4.59, 15.02 ± 1.25, and 4.27 ± 1.48 mg/g TAE, respectively. The DPPH activity between methanol and ethanol extracts showed no significant difference. The FRAP activity also showed no significant difference (P > 0.05) among the three solvents. There were significant differences between the wet and dry seasons in the phytochemical content. There was no recorded significant difference in the DPPH activity between the dry and wet season in all AEZs. FRAP was significantly higher in the dry season than the wet season for R. officinalis leaves harvested in all agro-agroecological zones except Thika. There were significant differences in phytochemical content and antioxidant activity between the agro-ecological zones (p < 0.05) except for the TFC. Conclusions The data obtained from this study demonstrated that hydro-alcoholic /methanolic and aqueous maceration systems extracted bioactive compounds from R. officinalis with high potential for applications in industries. The R. officinalis from different agro-ecological zones contained variable phytochemical composition, suggesting that geographical location and climatic conditions influence the biosynthesis and accumulation of secondary metabolites and other bioactive compounds. The data provided in this study will be crucial for processors to select the optimal harvesting season for the extraction of desired bioactive compounds from Rosmarinus officinalis.